Comparison of the Efficiency of Magnetic-Activated Cell Sorting (MACS) and Physiological Intracytoplasmic Sperm Injection (PICSI) for Sperm Selection in Cases with Unexplained Infertility - A Ahmadi; A Sobhani; MA Khalili; A Agha-Rahimi; A Nabi; N Findikli (JRI, 2022)
Background: The cases with unexplained infertility may have an abnormality in their sperm chromatin structure. Sperm selection methods can be used to separate sperm with low DNA fragmentation. The purpose of this study was to compare the efficacy of physiological intracytoplasmic sperm injection (PICSI) with magnetic-activated cell sorting (MACS) in assisted reproductive techniques in cases with unexplained infertility. Methods: The semen samples were collected from couples with unexplained infertility. After semen analysis and sperm DNA fragmentation (SDF) evaluations, samples were prepared with swim-up method. The rates of SDF in different fractions including raw semen (n=20), swim-up (n=20), only motile sperm after swim-up (swim-up selection) (n=20), MACS sperm selection (n=20), only motile sperm after MACS (MACS selection) (n=20), and PICSI sperm selection (n=16) were evaluated. Also, the main sperm characteristics and fine morphology of sperm suspension after MACS were assessed. Statistical analysis was performed using GraphPad Prism. The p<0.05 was considered statistically significant. Results: DNA fragmentation index (DFI) values in PICSI and MACS groups were significantly reduced as compared to the swim-up group. The rate of this reduction was more pronounced in MACS (58.20±13.02) than PICSI (36.57±15.52) group. Also, our results showed that MACS resulted in decreased sperm motility, with no alteration in their fine morphology. Conclusion: MACS was found to be more efficient in reduction of SDF rates than PICSI. However, none of the sperm selection techniques can not totally eliminated the spermatozoa with DNA fragmentation in the final sperm sample.